Which Factors Influence Learners’ Visual Attention to Images in Geographic Learning Media? - Behnke, Yvonne (Journal of Geography Education, 2023)
An eye-tracking and questionnaire-based study investigated possible factors influencing visual attention (e.g., usability, interest, and media preferences) when learning with photos, graphics, and maps. Data from 58 learners (14–17 years, secondary school) were analyzed. Three Geography textbook spreads on three interest-led topics (earthquakes, rainforests, agriculture) served as stimuli. Factor analysis identified relevant factors for learners’ visual attention to photos, graphics, and maps in the investigated textbook spreads. Usability, text preference, image preference, and individual interest (topic earthquakes) explained 48.5 per cent of the variance (most relevant factor: usability). Individual interest was less relevant than situational interest. Based on these findings, the paper presents suggestions to support teaching and learning with multimodal geographic learning media.